2019
DOI: 10.1039/c9ra00038k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular flexibility on the rheological and filtration properties of synthetic polymers used as fluid loss additives in water-based drilling fluid

Abstract: The effect of molecular flexibility on the rheological and filtration properties of synthetic polymers used as fluid loss additives in water-based drilling fluid was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…Therefore, how to improve the high‐temperature resistance of copolymer type filtrate reducers is one of the hot research topics. It was confirmed that increasing the proportion of rigid monomers in the main chain is propitious to maintain the properties of WBDFs at high temperature 17,33 …”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Therefore, how to improve the high‐temperature resistance of copolymer type filtrate reducers is one of the hot research topics. It was confirmed that increasing the proportion of rigid monomers in the main chain is propitious to maintain the properties of WBDFs at high temperature 17,33 …”
Section: Introductionmentioning
confidence: 84%
“…The flow characteristic of drilling fluids plays a vital role to solve the drilling problems (such as carry and suspend rock cuttings, ensure hole cleaning). The filtration property refers to the formation of a thin and dense filter cake on the borehole wall by the solid particles in the drilling fluid under the effect of pressure difference between the hydrostatic column pressure of drilling fluid and pressure of fluid in formation pore to prevent the invasion of water into permeable formation 17 . It is directly related to reservoir protection and wellbore stability.…”
Section: Introductionmentioning
confidence: 99%
“…Drilling fluid formulations-OBM1, OBM2, and OBM3-with various additives. Oil to water phase ratio was 70:30 and the drilling fluid density is 1.61 g/cm 3 . Priamine 1074, Lime, VersaMul, VersaCoat, VersaTrol HT, and barite are commercial trade names of the drilling fluid additives.…”
Section: Synthesis Of Msil-oh Msil-c16 and Msil-ph Organically Modmentioning
confidence: 99%
“…Priamine 1074, Lime, VersaMul, VersaCoat, VersaTrol HT, and barite are commercial trade names of the drilling fluid additives. The density of CaCl 2 brine is 1.1 g/cm 3 . 50 g of Ca-montmorillonite (RevDust) was added into each OBM to replicate the drilled rock contamination effect that occurs during drilling operations.…”
Section: Synthesis Of Msil-oh Msil-c16 and Msil-ph Organically Modmentioning
confidence: 99%
See 1 more Smart Citation